Hamilton, the revolution : being the complete libretto of the Broadway musical, with a true account of its creation, and concise remarks on hip-hop, the power of stories, and the new America /: being the complete libretto of the Broadway musical, with a true account of its creation, and concise remarks on hip-hop, the power of stories, and the new America. (2016) - Miranda, Lin-Manuel, 1980-; McCarter, Jeremy, 1976-
No abstract available